A STUDY OF KNOWLEDGE, ATTITUDE, AND PRACTICE OF PHARMACOVIGILANCE AMONG II-YEAR UNDERGRADUATE MEDICAL STUDENTS AND INTERNS AT A TERTIARY CARE TEACHING HOSPITAL - ANUSHA S; SRINATH S; KAVYA M (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Understanding the importance of adverse drug reactions (ADRs) reporting in a timely and accurate manner is essential for the success of pharmacovigilance. The underreporting or delayed reporting of ADRs can hinder the effectiveness of pharmacovigilance efforts. Assessing the knowledge, attitude, and practice (KAP) of pharmacovigilance among medical students and interns is indeed crucial as they are future health-care practitioners. Methods: The study was carried out at the tertiary care teaching hospital in Kallakurichi after receiving approval from the Institutional Ethics Committee of the Government Medical College, Kallakurichi. The participants of the study included interns and II-year MBBS students. They were enrolled in the study and given a questionnaire on the KAP of pharmacovigilance through Google Forms. The collected responses were analyzed using Microsoft Excel, and the findings were presented in the form of percentages. Results: In the knowledge domain, 85.2% of participants demonstrated awareness regarding the individuals responsible for reporting ADRs. In the attitude domain, according to 92.8% of participants, pharmacovigilance and ADR should be integrated into the undergraduate curriculum. However, in the practice domain, the percentage of participants who actually practiced reporting ADRs was lower (33%). Despite the majority of participants exhibiting commendable knowledge and attitude, a noticeable disparity was observed in their practical implementation. Conclusion: Our study has shown the importance of raising awareness on ADR reporting along with the recommendation for effective training in institutions and health-care centers, which is crucial for bridging the existing gap.